Prestasi Belajar Bahasa Inggris Mahasiswa yang Belajar dan yang Tidak Bahasa Inggris di Sekolah Dasar - Gusri Emiyati Ali; Naely Muchtar (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
This study is based on the Cryptical Period Hypothesis by Lenneberg (1976) which states that ages 2 to 12 are ideal for achieving language skills like native speakers of a foreign language. Based on this hypothesis, the most appropriate time for Indonesian children to learn English as a foreign language is in elementary school. However, government policy through the 2013 curriculum no longer requires children in elementary school to learn English. Therefore, this study aims to compare the learning achievement of students between those who study and those who do not learn English in primary schools. This research is very important to be carried out for consideration by the government in determining policies related to learning English in elementary schools. This research is a comparative descriptive study. The sample consisted of two groups that were selected through purposive sampling technique, namely those who studied and did not learn English in primary schools and did not attend previous English courses. Data are grouped, as a percentage, and then compared. The results showed that students who studied English in primary schools had better English learning achievement than students who did not learn English in primary schools.